Perm national research polytechnic university development programme. The equator: results and further tasks - Tashkinov, A.A.; Makarevich, V.I. (Perm Federal Research Centre Journal, 2015)
PNRPU is completing the second stage of its development as a national research university. The article presents the main large-scale changes in all the spheres of universtity activities: in education, science, innovations, and international links. New objectives are set for intensifying the implementation of the programme.